The Application of Therapeutic Relationships in Psychiatric Patients: The Role of Psychiatric Nurses, Communication Techniques, and Case Application - Thoin, Pasinee; Srioad, Phatanee (Journal of The Royal Thai Army Nurses, 2025)
Building a therapeutic relationship with psychiatric patients is a crucial process in psychiatric care. Nurses must use themselves as a therapeutic tool from beginning to end, aiming to help patients understand their problems and find appropriate solutions on their own. The role of psychiatric nurses is crucial in the support and treatment process, particularly in accessing services and cooperating with medical treatment. Patients with cognitive, emotional, and behavioral disorders impacting their lives, self-care, and social interactions. Therefore, the role of nurses requires learning techniques and methods for building relationships in all four stages: Stage 1: Before Interaction: Nurses prepare the patient emotionally, knowledgeably, and with information; Stage 2: Initial Stage: Nurses build trust, establish agreements, and explore the problem; Stage 3: Problem-solving: Nurses maintain a good relationship and assist the patient in analyzing the problem, planning, and promoting behavioral change; and Stage 4: Ending the Relationship: Nurses assist in evaluating and summarizing the relationship and preparing the patient for a stable return to society. This article aims to present guidelines for practice, the role of psychiatric nurses, and their application in therapy and research. This will enable them to apply this knowledge to nursing practice and assist and resolve their own and psychiatric patient problems, resulting in positive treatment outcomes and preventing conflicts between nurses and patients or their families. This leads to cooperation in solving problems appropriately and creating sustainable change. Patients can return to live appropriately in society within an ethical framework and acceptance of individual differences.